Ancestry, Language and Culture - Enrico Spolaore; Romain Wacziarg (Center for Economic Studies and ifo Institute (CESifo), 2015)
We explore the interrelationships between various measures of cultural distance. We first discuss measures of genetic distance, used in the recent economics literature to capture the degree of relatedness between countries. We next describe several classes of measures of lin-guistic, religious, and cultural distances. We introduce new measures of cultural distance based on differences in average answers to questions from the World Values Survey. Using a simple theoretical model we hypothesize that ancestral distance, measured by genetic distance, is positively correlated with linguistic, religious, and cultural distance. An empirical exploration of these correlations shows this to be the case. This empirical evidence is consistent with the view that genetic distance is a summary statistic for a wide array of cultural traits transmitted intergenerationally.
Keywords: Z10; 330